Optimizing the manufacturing process to increase fill factor and elevate efficiency of n-type crystalline silicon TOPCon solar cells - Wenjing Xu; Pengyu Zhou; Qi Xiu; Xianbang Xing (AIP Advances, 2025)
The growth of the photovoltaics industry is driven by advancements in solar cell conversion efficiency and manufacturing processes. While passivated emitter and rear cell solar cells achieve around 23% efficiency, tunnel oxide passivated contact (TOPCon) technology offers a 1.5%–2% efficiency gain. However, this still falls short of the theoretical limit for TOPCon solar cells. This study investigates methods to enhance fill factor and overall efficiency by optimizing key manufacturing processes. By reducing series resistance and improving shunt resistance, the optimized TOPCon solar cells demonstrated efficiency improvements of 0.24% and 0.11%, respectively. Combining these optimizations, a potential efficiency gain of 0.35% could be achievable compared with current TOPCon solar cells. These findings highlight the potential for further efficiency improvements through continued process optimization and contribute to the advancement of the photovoltaic industry.